VARIABILITY STRUCTURE AND GENETIC DETERMINATION OF PLANT PHENOLOGICAL TYPE (ACCORDING TO RESULTS OF TOBACCO RESEARCH) - A. E. Shpakov; Yu. A. Volchkov; V. V. Drobyshev (Вавиловский журнал генетики и селекции)
The objectives of the study were the detection of phenological traits essential for the evaluation of genetically determined differences in phenological type in tobacco and investigation of their genetics. Analysis of the variation pattern of the phenological trait complex in a tobacco variety collection showed no difference in the genetic determination between the vegetative and generative periods of tobacco plant development. Six genotype classes were found in the collection with regard to phenological type. The mode of independence between the genetic systems operating at the vegetative and generative stages of tobacco development was considered by logical analysis of relationships among the terms genotype, phenological type, and genetic program with the use of the set theory.